Aurality of images in graphic ethnographies: Sexual violence during wars and memories of the feelings of fear. Issue 4 (July 2022) - Mookherjee, Nayanika
This article examines the role of graphic ethnography in mapping the objects and feelings of fear through the silence of images, through the aurality of this silence. By aurality, I refer to the sounds and feelings felt by the reader when seeing these images in their colours, visuality and contexts which are not brought out by words and texts alone. The article explores the new sociographies that emerge from this intercitationality of visceral fear, from the aurality of this dread, that survivors of sexual violence during the Bangladesh war of 1971 feel till today. It suggests that we need to go beyond the search for the 'unsayable and unseeable' to understand how survivors and their quotidian existence are intertwined with these objects of fear. Nothing is unseeable or unsayable for survivors here as they live through fear 'as an environment'. The article explores the intertextual, intercitational registers between my book The Spectral Wound and my co-authored graphic novel, Birangona, in order to bring out the reparative aspects of graphic ethnography and the new forms of knowledge production.